The Relationship Between Academic Supervision and Learning Motivation with Learning Outcomes of 5th Grade Elementary School in Region I, Bolano District - Cahyono, Cahyono; Amus, Sunarto; Kadarisman, Kadarisman (Sebatik, 2024)
Supervision is an effort by leaders to help teachers to carry out their duties better. The purpose of this study was to determine the significant relationship between academic supervision and learning motivation, the significant relationship between academic supervision and learning outcomes, the significant relationship between learning motivation and learning outcomes and the significant relationship between academic supervision and learning motivation and learning outcomes. The type of quantitative research uses a combination of ex-post facto methods and survey methods with a correlational approach. The subjects of the study were all principals and elementary school teachers in Region I of Bolano Regency, totaling 58 people and 5th grade elementary school students in Region I of Bolano Regency. Data collection techniques used questionnaires, interviews and documentation. Data analysis techniques were correlation, simple linear regression analysis, multiple linear regression and One Way Anova test. The results of the study indicate that there is a positive and significant relationship between academic supervision and student learning motivation with a correlation coefficient (r) of 0.671 in a strong significance category of 0.000 <0.05, a calculated t value of 8.2674, there is a positive and significant relationship between academic supervision and student learning outcomes with a correlation coefficient (r) of 0.865 in a very strong category with a significance value of 0.000 <0.05 and a calculated t value of 12.871 significant 0.000. The calculated F value of 165.667, there is a positive and significant relationship between learning motivation and student learning outcomes with a correlation coefficient (r) of 0.846 in a very strong category with a significance value of 0.000 <0.05 and a calculated t value of 12.004 significant 0.000. The calculated F value is 144.084 and there is a positive and significant relationship between academic supervision and learning motivation simultaneously on student learning outcomes with a correlation coefficient (R2) of 87.40% and a calculated F value of 190.3364. So it can be concluded that the principal's academic supervision and learning motivation have a strong influence on improving student learning outcomes.